Manganese exposure and its U-shaped relationship with diabetic retinopathy: analysis of NHANES 2011–2020 - Chen, Xi; Gu, Zhenzhen; Qi, Yixin; Hao, Xiaofeng; Xie, Like (Frontiers in Nutrition, 2025)
BackgroundAlthough many studies have pointed to the role of manganese in various diseases. However, there are surprisingly few studies on the potential relationship between manganese and diabetic retinopathy (DR). The available literature fails to provide definitive conclusions regarding the directionality and strength of this particular association.MethodsThe analytical cohort comprised 2,558 adults from NHANES 2011–2020 cycles. We employed binary logistic regression to evaluate manganese-DR associations, supplemented by subgroup analyses, nonparametric smoothing techniques, and propensity score weighting to address potential confounding.ResultsOur multivariate model failed to find a significant linear relationship between manganese concentration and the likelihood of DR (p > 0.05). However, we found that manganese levels above 7.66 μg/L DR were less severe (adjusted OR = 0.84, p = 0.0007). This suggests a nonlinear dose–response relationship.ConclusionThe manganese and DR relationship followed a U-shaped dose–response pattern. The least severe condition was observed at 7.66 μg/L, while the disease was aggravated at both insufficient and excessive concentrations.